Lichenicidin rational site‐directed mutagenesis library: A tool to generate bioengineered lantibiotics. Issue 11 (8th August 2019) - Barbosa, Joana; Caetano, Tânia; Mösker, Eva; Süssmuth, Roderich; Mendo, Sónia
Abstract: Lantibiotics are ribosomally synthesized and posttranslationally modified antimicrobial peptides that arise as an alternative to the traditional antibiotics. Lichenicidin is active against clinically relevant bacteria and it was the first lantibiotic to be fully produced in vivo in the Gram‐negative host Escherichia coli . Here, we present the results of a library of lichenicidin mutants, in which the mutations were generated based on the extensive bibliographical search available for other lantibiotics. The antibacterial activity of two‐peptide lantibiotics, as is lichenicidin, requires the synergistic activity of two peptides. We established a method that allows screening for bioactivity which does not require the purification of the complementary peptide. It is an inexpensive, fast and user‐friendly method that can be scaled up to screen large libraries of bioengineered two‐peptide lantibiotics. The applied system is reliable and robust because, in general, the results obtained corroborate structure–activity relationship studies carried out for other lantibiotics. Abstract : A site directed mutagenesis library was generated for the lantibiotic lichenicidin. Additionally, a new bioassay method was developed and showed to be very effective for the screening of two‐peptide lantibiotics libraries. As for other lantibiotics, Bliα:Glu26 is crucial for lichenicidin's bioactivity; alteration of the peptide structure was important to elucidate lichenicidin's structure–activity relationship and showed that Ser and Thr residues can be interchangeable for ring formation. This study contributes with guidelines of possible approaches to apply in the directed evolution of lantibiotics.